Knowledge and practice regarding menstrual hygiene among physically disabled women in Kathmandu, Nepal - Pokhrel, Bishal; Mahat, Sunita; Parajuli, Kritri (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Disability is the condition of difficulty in carrying out daily activities normally and in taking part in social life due to problems in parts of the body and the physical system. Disability also carries stigma, so disabled people may face layers of discrimination when they are menstruating. The objective of the review is to assess the menstrual hygiene practice of disabled women, the barriers they face, and the available interventions to help them manage their menstruation hygienically and with dignity. Material and Methods: This was a cross-sectional descriptive study that was conducted among 151 physically disabled peoples.Self-structured questionnaire and face-to-face interview was used as data collection tools and techniques. Data entry and analysis was done using SPSS 16.0. The results of the study were presented with the help of tabular description using the same software along with Microsoft word and excel 2007. Results: Most of respondents knew the 26-30 days as normal cycle duration (80.13%). Majority of respondents had reported that they do not go to holy places (91.39%) and should not cook food (94.03%) during menstruation. Most of respondents had stayed (96.68%) and eat (98.01%) at same place and 31.38% of respondents had bath daily during menstruation. 83.44% of respondents used sanitary while 69.53 % of respondents changed pad twice a day. Maximum number of the respondents 91.39% disposed sanitary pad in dustbin. 87.41% of respondents learned about menstrual hygiene from parents. Conclusion: Good and satisfactory knowledge about menstrual hygiene was found among girls of age group 15-24years.